2010
DOI: 10.1073/pnas.1005874107
|View full text |Cite
|
Sign up to set email alerts
|

Substantial nitrogen acquisition by arbuscular mycorrhizal fungi from organic material has implications for N cycling

Abstract: Arbuscular mycorrhizal (AM) fungi are obligate biotrophs that acquire carbon (C) solely from host plants. AM fungi can proliferate hyphae in, and acquire nitrogen (N) from, organic matter. Although they can transfer some of that N to plants, we tested the hypothesis that organic matter is an important N source for the AM fungi themselves. We grew pairs of plants with and without the AM fungus Glomus hoi in microcosms that allowed only the fungus access to a 15 N/ 13 C-labeled organic patch; in some cases, one … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

21
390
4
7

Year Published

2011
2011
2023
2023

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 586 publications
(445 citation statements)
references
References 37 publications
(43 reference statements)
21
390
4
7
Order By: Relevance
“…Such effects could depend on both the competition for N and photosynthates between AM fungi and flowers (Johnson et al 1982) and the ability of AM fungi to reduce nutrient deficiency or other stresses for the host plant. The number of flower-bearing stems is determined earlier than the number of flowers per stem (Slafer et al 1996), and AM fungi retain most of the N taken up in organic form for their own growth (Hodge and Fitter 2010). The growth substrate used in the present study was rich in organic matter.…”
Section: Discussionmentioning
confidence: 99%
“…Such effects could depend on both the competition for N and photosynthates between AM fungi and flowers (Johnson et al 1982) and the ability of AM fungi to reduce nutrient deficiency or other stresses for the host plant. The number of flower-bearing stems is determined earlier than the number of flowers per stem (Slafer et al 1996), and AM fungi retain most of the N taken up in organic form for their own growth (Hodge and Fitter 2010). The growth substrate used in the present study was rich in organic matter.…”
Section: Discussionmentioning
confidence: 99%
“…Experiments with pairs of plants with and without arbuscular mycorrhiza fungi showed that the fungus increased plant grows and N content (Hodge and Fitter, 2010). A study of babassu palm roots revealed root diameters in excess of 2 mm, which indicates abundance of mycorrhiza, and another study found a characteristic arbuscalar mycorrhizal species composition under babassu dominated sites (unpublished data, Christoph Gehring).…”
Section: Stemflow Solute Concentrations Of Trees and Palmsmentioning
confidence: 99%
“…Several studies also show that AMF influence bacterial communities inhabiting the rhizosphere and mycorrhizosphere (Ames et al, 1984;Scheublin et al, 2010), including shifts in denitrifying communities (Amora-Lazcano et al, 1998;Veresoglou et al, 2012b). AMF influence the N cycle and can take up significant amounts of nitrogen (Hodge and Fitter, 2010;Veresoglou et al, 2012a). By reducing the availability of soluble N in the soil, AMF could also reduce denitrification and N 2 O emission rates.…”
Section: Introductionmentioning
confidence: 99%